(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2022)
Introduction. In the period of transformational changes, integration of the higher education system into the world education space and its permanent reform, determining the effective activities of universities, their place in the rankings and on the market of educational and scientific services occupies a leading position in management. The purpose of the article. The purpose of the article is to form KPIs to assess the results of educational and scientific activities of Ukrainian higher education institutions (HEIs), improvement of their financial capacity, as well as increase in the effectiveness of financial and economic activities. Results. Foreign experience of the implementation of HEIs development strategies on the basis of a clear definition of KPIs, in particular, financial ones, is studied. Examining the goals and objectives of Ukrainian universities, their development strategies, and comparing them with world prominent HEIs, we see a clear similarity in the development of fundraising activities and increase in cooperation with the market environment, stakeholders, alumni, donors, philanthropists and others. However, transparency and publicity, development of methods and mechanisms of financial management, definition of clear KPIs remain relevant issues for Ukrainian HEIs nowadays. Conclusions. We consider that achieving a level of competitive HEI is not possible without a development strategy with defined strategic, tactical and current goals, clear tasks and monitoring of their implementation. It is proposed to launch the system of KPIs for HEIs and its application in the process of financial management which will foster achieving the results and transparency of HEI activity. In our opinion, defining common KPIs and their obligatory implementation will allow a chief funds administrator to monitor and timely adjust, if necessary, his/her actions, conduct a comparative assessment of the entire higher education system, and university management provide analysis, control and increase in performance and financial capacity, while stakeholders have access to reliable information. The fulfillment of this set of tasks and goals, the achievement of KPIs, in particular, financial ones will permit to form a strong financial potential of HEI, its development strategy and ensure financial stability and, consequently, competitiveness on the global market of educational and scientific services.